Phubbing Memicu Munculnya Sikap Apatis Siswa Terhadap Guru Dalam Pembelajaran Bahasa Indonesia SMA Di Bandung - Dea Ardelia; Jevina Nur Efendi; Hanifah Az Zahra; Najah Aminah Ridwan (Lembaga Pengembangan Kinerja Dosen, 2024)
Phubbing comes from a combination of phone and snubbing, which is defined as an attitude of hurting the interlocutor by using a smartphone excessively. This study aims to determine the relationship or correlation between apathy and the phubbing phenomenon and identify the impact of the phubbing phenomenon on the Indonesian language learning process of high school / equivalent in Bandung. This research uses quantitative methods by using respondents as research subjects. The data source was obtained by the authors using a survey method where the authors distributed questionnaires to respondents directly and through an online questionnaire (google form). The results showed a correlation indicating that phubbing does not contribute to the increase of apathy in the adolescent population in the process of learning Indonesian language at SMA / equivalent in Bandung. The psychosocial implications of these findings open up room for the development of better intervention strategies in managing gadget use among adolescents to promote mental health and more positive social interactions.